Analysis of Indonesian Language Errors in the YouTube Comment Section of the “Kenapa Mereka Bersatu Sih?” Content on the Raditya Dika Channel - Elli Novita Hutasoit; Martua Reynhat Sitanggang Gusar; Winny Tiara Manalu; Putri L. Sihombing; Lastri Juliarni Dongoran (Universitas Pakuan, 2026)
The YouTube comment section is a digital communication space that reveals diverse uses of the Indonesian language, including the emergence of various language errors influenced by non-formal language varieties. This phenomenon is important to study because it reflects the dynamics of Indonesian language use on social media and serves as an indicator of changes in the community’s language behavior. This study aims to describe and analyze the forms of Indonesian language errors found in the comment section of the video “Kenapa Mereka Bersatu Sih?” on Raditya Dika’s YouTube channel. The study employs a descriptive, qualitative approach. The research data consist of words, phrases, and sentences containing language errors, obtained through the observing (simak) and note-taking (catat) techniques. Data analysis was conducted using a classification of language errors at the phonological, morphological, semantic, and syntactic levels. The results show that language errors were found at all four levels, with a predominance of phonological errors, which include phoneme change, phoneme omission, and monophthongization. Morphological errors are marked by the incorrect writing of clitics and the omission of affixes. In contrast, semantic errors take the form of shifts in associative meaning and the broadening of meaning. Syntactic errors, meanwhile, appear in the non-standard sentence structures that affect the clarity of message delivery. The findings indicate that the characteristics of digital communication encourage the use of language forms that deviate from standard Indonesian grammar, due to the dominance of the oral variety, linguistic economy, and communication culture on social media. This study is expected to enrich the field of digital linguistics, particularly the analysis of language errors on social media, and to serve as a reference for the development of digital language literacy. Keywords: digital linguistics, Indonesian language, language errors, social media, YouTube comments.